Self healing concrete by incorporating palm oil fuel ash (POFA) as cement replacement material - Muhd Azzuhry, Zafri (2010)
Malaysia as The world largest exporter of palm oil has been facing problem in disposing palm oil fuel ash (POFA), a by product of palm oil mill. Previous researchers were revealing the potential of this finely ground waste as a partial cement replacement in reacted as pozzolans to produce a self healing concrete. In this study, the effectiveness using POFA as cement replacement material towards self healing of concrete were investigated. Four series of mix formulation in producing IOFA concrete with different percentage of cement replacement namely 0%, 10%, 20% and 30% were designed. All specimens were subjected to compressive strength due to 7,28,60 and days cured in water. In addition, the UPV test was conducted in order to monitor self healing progress of POFA concrete specimens due to hairline crack. The specimens were tested at different curing types subjected to UPV test. It was found that, the concrete with 20% of POFA recorded highest compressive strength compare to those mixes. It also revealed that, the UPV values were increases correspondingly to curing ages when POFA concrete immersed in water curing type. it shows the water curing were the effective mechanism towards self healing process.